The Endocannabinoid System and Oligodendrocytes in Health and Disease - Ilyasov, Alexander A.; Milligan, Carolanne E.; Pharr, Emily P.; Howlett, Allyn C. (Frontiers in Neuroscience, 2018)
Cannabinoid-based interventions are being explored for a range of central nervous system (CNS) pathologies such as neurodegeneration, demyelination, epilepsy, stroke, and trauma. As many of these disease states involve dysregulation of myelin integrity and/or remyelination, it is important to consider effects of the endocannabinoid system on oligodendrocytes and their precursors. To date, cannabinoid ligands and modulators of the endocannabinoid system have been shown to promote cell signaling in oligodendrocyte precursor survival, proliferation, migration and differentiation, and mature oligodendrocyte survival and myelination. In this review, we examine research reports on the effects of the endocannabinoid system components on oligodendrocytes and their precursors, with a focus on therapeutic implications.